1994
DOI: 10.3109/07420529409067794
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Function of Blood Monocytes Obtained from Healthy Nonsmokers, Asymptomatic Smokers, and Smokers with Chronic Bronchitis

Abstract: The present study focused on two questions: What effects do cigarette smoking and chronic bronchitis have on the function of the precursors of alveolar macrophages, the blood monocytes? Can seasonal variations affect the function of these cells? Phagocytic activity (the proportion of yeast-ingesting cells and the mean number of yeast particles per ingesting cell) and metabolism of arachidonic acid [secretion of prostaglandin E2 (PGE2) and leukotriene B4 (LTB4) in zymosan-stimulated cultures] were studied as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…One patient had distant metastases at the time of inclusion. The primary sites of the carcinomas were: maxilla (2), oral cavity (18), pharynx (21) and larynx (29). Blood samples for monocytes were drawn from both cancer and control patients at the bedside at 8 a.m. of a day in hospital prior to treatment in order to ensure a minimum level of stress within both groups as well as comparable physical activity prior to sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient had distant metastases at the time of inclusion. The primary sites of the carcinomas were: maxilla (2), oral cavity (18), pharynx (21) and larynx (29). Blood samples for monocytes were drawn from both cancer and control patients at the bedside at 8 a.m. of a day in hospital prior to treatment in order to ensure a minimum level of stress within both groups as well as comparable physical activity prior to sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as the different extent of stress [2], amount of physical activity prior to blood sampling [5], smoking habits [21] and alcohol consumption [22] between cancer and control groups might all per se cause a changed monocyte responsiveness. Previous studies have shown that the exclusion of the various confounding factors from a cancer/control study of the peripheral blood immune system is important to determine the T-lymphocyte in vitro responsiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…The possible factors modulating the immune response in different seasons and at different temperatures has been studied by some groups. The warmer temperature can facilitate the locomotion of human neutrophilic leukocytes and lymphoblasts [34,35] and thereby induce the release of inflammatory mediators, such as interleukin (IL)-6 [36,37]. These fluctuations in immune function in the different seasons may explain the seasonal variations in symptom flares of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal differences in the lymphocytic responses of men and women have been previously reported. [18] Additionally, differential seasonal effects of some hormones in both boys and girls have been described. [25] Similar factors may play roles in the sex-related difference in IC and TS frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In this context, seasonal variation in many medical diseases has been investigated. [16][17][18] To the best of our knowledge, no study to date has focused on the seasonality of IC and TS.…”
Section: Introductionmentioning
confidence: 99%